Ethanol and caffeine consumption modulates the expression of miRNAs in the cerebellum and plasma of UChB rats - Rossetto, I. M.U.; Cagnon, V. H.A.; Lizarte, F. S.N.; Tirapelli, L. F.; Tirapelli, D. P.C.; Arantes, R. M.S.; Chuffa, L. G.A. [UNESP]; Martinez, F. E. [UNESP]; Martinez, M. (Elsevier, 2019)
Aims: The present study aimed to verify changes in cerebellar and plasmatic expression of miRNAs after the chronic consumption of ethanol and caffeine in the UChB rat, an experimental model for alcoholism. Material and methods: Male rats at 5 months of age, were divided into the following groups (n = 10/group): 1. Ethanol (UChB rats receiving 10% ethanol solution and water ad libitum); 2. Ethanol + caffeine (UChB rats receiving 10% ethanol solution + 3g/l caffeine and water ad libitum); 3. Control (rats receiving water ad libitum). The cerebellum and plasma of the animals were collected and processed by RT-PCR for the miRNAs-155-5p, -146a-5p, -126-3p, -132-3p, -339-5p. Key findings: Ethanol and caffeine were capable of regulating the expression of miRNAs associated with the inflammatory process in the tissue and plasma of the UChB rats. Increased expression of the analyzed miRNAs-155-5p, -146a-5p, -126-3p, -132-3p was observed for the cerebellar tissue in the Ethanol group and reduced expression of them in the Ethanol + caffeine group. In plasma, caffeine significantly elevated the miR-126-3p and miR-132-3p levels and decreased miR-155-5p levels. Ethanol consumption increased miR-146a-5p expression and decreased miR-339-5p levels. In brief, altered plasmatic levels of the miRNAs did not reflect the miRNAs levels found in cerebellar tissue. Significance: Considering the results herein, we concluded that ethanol predisposes to an inflammatory process while caffeine has a neuroprotective effect on the cerebellar tissue.
Keywords: Caffeine; Cerebellum; Ethanol; miRNA; Plasma; UChB rats